Square of a Sum (a + b)2
How to solve the square of a sum (a + b)^2: formula, 1 example, and its solution.
(a + b)2 = a2 + 2ab + b2
The middle sign in (a + b)2 is plus.
So the middle term of the right side, +2ab, is also plus.
This is the difference between
the (a + b)2 formula and the (a - b)2 formula.
First square the first term: x2.
The middle sign in (x + 3)2 is plus.
the first term, x times,
the last term, 3.
Square the last term: +32.
So (x + 3)2 = x2 + 2⋅x⋅3 + 32.
+2⋅x⋅3 = +6x
+32 = +9
So x2 + 6x + 9 is the answer.